Swelling-induced pore generation in fluorinated polynorbornene block copolymer films. Issue 25 (15th June 2018) - Cho, Yunshik; Kim, Youngjin; Choi, Tae-Lim; Lim, Jeewoo; Char, Kookheon
Abstract : Synthesis of fluorinated polynorbornene BCPs and swelling-induced pore generation of their films using fluorous solvent. Abstract : Selective swelling of block copolymer (BCP) films is an emerging method for preparing mesoporous polymer films. Materials used in this simple and mild pore-generation strategy, however, have been limited to polystyrene BCPs with hydrophilic minority blocks, the swelling of which is conducted in highly polar solvents. This often results in swollen films with hydrophilic surfaces. To expand the field of application of porous films obtained by this method, the variety in both materials used and surface properties obtained needs to be established. This work describes the preparation of fluoroalkylated polynorbornene BCPs and fluorous solvent-induced pore generation of these BCP films. The resulting mesoporous films are highly hydrophobic and provide a handle for controlling the refractive index over a wide range of nearly 0.3. Furthermore, hierarchical porous structures have been achieved using orthogonal non-solvent vapor-induced phase separation using water vapor followed by selective swelling in a fluorous solvent. This work represents the first application of the fluorous polymer system in selective solvent-induced pore generation of BCPs.